Emerging treatment options for the treatment of moderate to severe plaque psoriasis and psoriatic arthritis: evaluating bimekizumab and its therapeutic potential [Corrigendum] - Chiricozzi A; De Simone C; Fossati B; Peris K (Dove Medical Press, 2019)
Chiricozzi A, De Simone C, Fossati B, Peris K. Psoriasis: Targets and Therapy. 2019;9:29–35.The authors of this paper have advised us that by mistake they uploaded the wrong figure files for Figures 2 and 3 which had not been correctly updated.Read the original article